Prehistory : A Very Short Introduction - Gosden, Chris (Oxford Oxford University Press, 2003)
Many of the familiar aspects of modern life are no more than a century or two old, yet our deep social structures and skills were in large measure developed by small bands of our prehistoric ancestors many millennia ago. The reader is invited to think seriously about who we are by considering who we have been
Include Illustrations and Index
Keywords: History, Ancient